(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The metaphorical EMOTION – LIQUID model is widely used in different world languages and has repeatedly been the object of linguistic research. The article aims to compare how the EMOTION – LIQUID model is implemented in the Kazakh and Russian languages at the level of semantic roles in which the designations of such basic emotions as sadness, joy, and anger can act. Examples of regular use of metaphors are selected using dictionary and corpus data. Applying the cluster approach in the study made it possible to cover the main designations of the emotions under consideration. Within the framework of research, special attention was also paid to the semantics of verbs and adjectives, which, on the one hand, maintain a connection with the source zone in metaphorical contexts and, on the other hand, form an idea of a particular semantic role and generally define a set of possible semantic roles within a given metaphorical model. The article describes the main systematic similarities and differences between languages in how EMOTION – LIQUID is conceptualized. As our analysis shows, in the Kazakh language, lexemes of the same cluster tend to perform the same semantic role. In contrast, there is a distribution of different lexemes in the Russian language in several semantic roles. The results obtained are valuable for semantic and comparative research. In particular, the analysis of semantic roles makes it possible to clarify significantly the application of a particular metaphorical model in a particular language. Keywords: metaphor, semantic role, emotions, Kazakh, Russian.